2023
DOI: 10.3389/fimmu.2023.1126457
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors and risk for asthma: A Mendelian randomization analysis

Abstract: BackgroundPrevious research has found a link between dietary factors and asthma. However, few studies have analyzed the relationship between dietary factors and asthma using Mendelian randomization. Methods: The IEU Open GWAS project (https://gwas.mrcieu.ac.uk/) was the source of exposure and outcome datasets. The exposure datasets included Alcoholic drinks per week, Alcohol intake frequency, Processed meat intake, Poultry intake, Beef intake, Non-oily fish intake, Oily fish intake, Pork intake, Lamb/mutton in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The intake of vitamins has also been found to affect IPF in clinical trials [ 11 ]. Dietary intake has been shown to have a causal relationship with asthma [ 12 ] and lung cancer [ 13 ]. The research on the causal relationship between dietary intake and IPF still needs to be improved, and the specific nutritional information related to IPF has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The intake of vitamins has also been found to affect IPF in clinical trials [ 11 ]. Dietary intake has been shown to have a causal relationship with asthma [ 12 ] and lung cancer [ 13 ]. The research on the causal relationship between dietary intake and IPF still needs to be improved, and the specific nutritional information related to IPF has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more research evidence is needed to justify this in the future. Similar to the results of previous MR analyses, our study also demonstrated that the intake of dried fruits can slow down the onset of asthma to a certain extent 48 . Unfortunately, through MR analysis, we did not find an exact dietary factor associated with the onset of OSA, and only explored some factors that may influence it.…”
Section: Discussionsupporting
confidence: 91%
“…The project, supported by the MRC Integrated Epidemiology Unit (IEU) at the University of Bristol, collates and analyses GWAS data from UK Biobank, published articles. This study was exempt from ethical review body approval as the data used in this study are open, anonymized and de-identi ed [14].…”
Section: Methodsmentioning
confidence: 99%